The Dynamics of Strategic ChangeThe Dynamics of Strategic Change, by HiningsC. R. and GreenwoodRoyston. Oxford, England: Basil Blackwell, 1988, 223 pp., $39.95, cloth. - Oliver, Christine (Academy of Management Review, 1991)
The article reviews the book “The Dynamics of Strategic Change,” by C.R. Hinings and Royston Greenwood.